# 6 and so forth thus we nd that a6 y a0 1 2p 2 22 pp

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ecursion formula for the coeﬃcients of the power series: an+2 = 2n − 2p an . (n + 2)(n + 1) (1.10) Just as in the case of the equation of simple harmonic motion, the ﬁrst two coeﬃcients a0 and a1 in the power series can be determined from the initial conditions, dy y (0) = a0 , (0) = a1 . dx The recursion formula can be used to determine the remaining coeﬃcients in the power series. Indeed it follows from (1.10) with n = 0 that a2 = − 2p a0 . 2·1 Similarly, it follows from (1.10) with n = 1 that a3 = 2 − 2p 2(p − 1) a1 = − a1 , 3·2 3! and with n = 2 that a4 = − 4 − 2p 2(2 − p) −2p 22 p(p − 2) a2 = a0 = a0 . 4·3 4·3 2 4! Continuing in this manner, we ﬁnd that a5 = 6 − 2p 2(3 − p) 2(1 − p) 22 (p − 1)(p − 3) a3 = a1 = a1 , 5·4 5·4 3! 5! 11 8 − 2p 2(3 − p) 22 (p − 2)p 23 p(p − 2)(p − 4) a4 = a0 = − a0 , 6·5·2 6·5 4! 6! and so forth. Thus we ﬁnd that a6 = y = a0 1 − 2p 2 22 p(p − 2) 4 23 p(p − 2)(p − 4) 6 x+ x− x + ··· 2! 4! 6! +...
View Full Document

## This document was uploaded on 01/12/2014.

Ask a homework question - tutors are online